An Automatic Pattern Grading Technique in Garment CAD (Journal of Fiber Bioengineering and Informatics, 2018)
This paper presents an automatic pattern grading technique by obtaining point grading rulesautomatically in order to avoid the manual input of cardinal point increments in the traditional GCADsystem. Based on the principles of the pattern grading and pattern structures, patterns are divided intotwo categories: basic patterns and fashion patterns that are derived from basic patterns. Since basicpatterns and fashion patterns are the specific form of 2D garment structure of human body, the gradingrule of the former has relationship with that of the latter quantitatively, thus the fashion patterns can begraded automatically by applying the grade rule data of basic patterns. This paper depicts the computerclass design scheme of the technique, including the construction of the pattern data structure, theacquirement of the grading rules of basic patterns by parameterization, the algorithms on the automatictransformation from the grading point increment of basic patterns to the one of fashion patterns and theapplication of grading rule of basic pattern in fashion patterns. The experiment results show that thetechnique is feasible.
Keywords: computer aided garment design; automatic pattern grading; basic pattern; fashion pattern; prototype